Bitwise : a life in code - Auerbach, David (David B.) (New York : Pantheon Books, 2018)
An exhilarating crossover between memoir and argument demonstrating how computers and algorithms shape our understanding of the world and who we are. As we engineer ever-more intricate algorithms to translate our experiences and narrow the gap that divides us from the machine, we willingly rub out our nuances and our idiosyncrasies--precisely that which makes us human. Bitwise is David Auerbach's thoughtful ode to the computer codes and languages that captured his imagination as a child, and a reflection of how he's both experienced and written the algorithms that have come to taxonomize human speech, knowledge, and behavior--and compel us to do the same. With a philosopher's sense of inquiry and an engineer's eye, Auerbach recounts his childhood spent drawing ferns with the programming language Logo on the Apple IIe, his adventures in early text-based video games, his schooling as an engineer, and his contributions to instant messaging technology developed for Microsoft and then to software built to sift through Google's data stores. His unsettling conclusion--that algorithms are standardizing and coarsening our own lives--is inescapable."--
Logo and love -- Chat wars -- Binaries -- Interlude: Foreign tongues -- Naming of parts -- Self-approximations -- Games computers play -- Interlude: Adventures with text -- Big data -- Programming my child -- Big human -- Epilogue: The reduction of language, the flattening of life.
Includes bibliographical references (pages 263-278) and index.
Keywords: Auerbach, David -- Philosophy; Computer science -- Philosophy; Computer science -- Social aspects; Computer scientists -- United States -- Biography